1991
DOI: 10.2466/pr0.1991.68.2.563
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effects of Travel and Study: The Semester at Sea Program

Abstract: Ten years after completion of a voyage, a random sample of 40 participants in the Semester at Sea Program were contacted by telephone and mail to explore possible long-term effects of the travel-study experience. Respondents answered open-ended questions about outcomes of Semester at Sea, and they completed the Purpose in Life Test of Crumbaugh. Participants maintained a global perspective, and they obtained high test scores. If they had become parents, the participants showed further discovery of meaning. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…It is assumed that the perception of a student who has not travelled is quite 46 International Research in Geographical and Environmental Education different from a student with international experience. Studies indicate that there have been a variety of changes in tourist attitudes as the result of travel to different locations (Pearce, 1980;Welds & Dukes, 1985;Dukes et al, 1991). In general a traveller tends to have a more favourable view of other cultures after completion of a trip to a foreign country (Welds & Dukes, 1985).…”
Section: An Evaluation Of the Influence Of Travel On The Geographic Kmentioning
confidence: 98%
“…It is assumed that the perception of a student who has not travelled is quite 46 International Research in Geographical and Environmental Education different from a student with international experience. Studies indicate that there have been a variety of changes in tourist attitudes as the result of travel to different locations (Pearce, 1980;Welds & Dukes, 1985;Dukes et al, 1991). In general a traveller tends to have a more favourable view of other cultures after completion of a trip to a foreign country (Welds & Dukes, 1985).…”
Section: An Evaluation Of the Influence Of Travel On The Geographic Kmentioning
confidence: 98%
“…Furthermore, students are expected to develop a global perspective and increase their cultural and intercultural competencies (Kang, 2018). Dukes et al (1991Dukes et al ( , 1994 and Duke (2006) have shown that students who have attended this programme experience positive longterm effects, such as creating a purpose in life, personal growth, meaningfulness, and becoming high achievers. The curriculum at SAS caters to promoting global education (Simmons & Strenecky, 1995).…”
Section: Semester At Sea (Sas) As a Global And Diverse Contact Zonementioning
confidence: 99%
“…For example, there are numerous articles describing the negative impact of culture shock, [13][14][15][16] reentry or reverse culture shock, [17][18][19][20][21][22][23][24][25] and evidence of maladjustment even years after students return. [26][27][28][29][30][31] These negative outcomes, have at times shackled students personally and professionally, depriving them of the full benefit of studying abroad that they sought when they applied to go abroad. [32][33][34][35][36] If even a relatively small number of study abroad nurse alumni find themselves coping with buried and/or unresolved grief as a result of the devastating suffering they have witnessed abroad, or if they are unable to make peace with their feelings of differentness, confusion, threat, loneliness, and disappointment in relationship to self and others that surfaced in-tandem with the study abroad experience, [37][38][39][40][41][42][43][44][45][46] might the full benefit of the study abroad experience be lost to these individuals, as well as to the global community they are preparing to serve?…”
Section: Introductionmentioning
confidence: 99%